Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Disiplin Kerja Karyawan pada PT Era Mulia Abadi Sejahtera - Aryanti, Ari Dwi; Setiadi, Pompong Budi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to ascertain how organizational culture and leadership style affect employee discipline in a workplace. Employees of PT Era Mulia Abadi Sejahtera in Malang City, East Java, were the subject of this study. This study employed quantitative methodologies in a descriptive research design. In order to collect primary data for this study, employees at PT Era Mulia Abadi Sejahtera in Malang, East Java, were given questionnaires to complete. The sample used in this study represents the entire workforce at the office. Multiple regression analysis, which is carried out using the SPSS program, is the analytical technique used. According to the study's findings, organizational culture and leadership style both influence employee work discipline favorably. The factors of leadership style and corporate culture also influence workers' work ethics at the same time.